PENGARUH TAMPILAN ETALASE, PENDEKATAN PROMOSI, GAYA HIDUP BERBELANJA, DAN KARYAWAN TOKO TERHADAP PEMBELIAN IMPULSIF PADA PENGUNJUNG HERMES PALACE MALL KOTA BANDA ACEH - Isra Mirandha, Iskandarsyah (Departemen Manajemen, 2017)
ABSTRACTThis study aims to examine the impact of window display, promotional approaches, shopping lifestyle and salesperson toward impulsive buying. The samples used in this study are visitors, who experience purchasing at Hermes Palace Mall Banda Aceh. A questionnaire was conducted as research instrumen for this research method. 211 respondents were analyzed by using puposive sampling technique. A Multiple Linear Regression (MLR) used to examine and analyze the hypotheses. The result of this study shows independent variables; promotioanal approaches, shopping lifestyle and salesperson have a positive and significant impact (sig 0,05) toward impulsive buying. Window display as independent variable however has a positive toward impulsive buying (sig 0,05).Key Word: Window Display, Promotional Approaches, Shopping Lifestyle, Salesperson, Impulsive Buying